The Influence of Halal, Food Safety and Quality on Students' Buying Decisions Using Structural Equation Modeling (SEM) Methods - Atika Salsabila; Hana Catur Wahyuni (Universitas Muhammadiyah Sidoarjo, 2022)
In today's era, technology is growing rapidly. People are very easy to access information through various media either directly or indirectly. Therefore, society as consumers is very selective in determining the products and services to be consumed. There are many factors behind consumers in product selection. Among them are in terms of idolatry, food safety and quality. Companies must be able to set standards in order to maintain consumer trust and loyalty. This study aims to find out the relationship between halal factors, food safety and quality in consumer buying decisions. The object of the study is the student. As a younger generation, students can show selective and conscientious attitude before choosing a product and also have control in determining the development of trends in the future. This study uses structural equation modeling (SEM) methods. The results of this study are that of the 4 hypotheses only 3 hypotheses are accepted. The accepted standard of a hypothesis is if the CR (Critical Ratio) value ≥1.967 and the value of P (Probability) ≤0.05. The three accepted hypotheses are first, the influence of halal on food security. Second, the effect of safety on quality. Third, the influence of quality on buying decisions. The rejected hypothesis that halal affects the quality does not meet the critical ratio standard of -1,993 so that the results are not significant.